Characterization of pitch prepared from pyrolysis fuel oil via electron beam irradiation. (June 2017) - Kim, Hong Gun; Park, Mira; Kim, Hak-Yong; Kwac, Lee Ku; Shin, Hye Kyoung
Abstract: Pitch samples were obtained from pyrolysis fuel oil by thermal treatment for 2 h at 300 °C after electron beam irradiation (EBI) treatment and by thermal treatment alone for different temperature of 250 °C, 300 °C, and 350 °C. EBI treatment was found to be an effective treatment for preparing pitch compare to the pitch obtained without EBI treatment. These results were confirmed by Fourier transform infrared spectroscopy (FT-IR) and Carbon-13 nuclear magnetic resonance ( 13 C NMR) analyses, which showed the increase in the intensities of peaks corresponding to aromatic compounds. In the matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) spectra, the amount of components with medium molecular weights in the pitch was found to increase with the temperature; likewise, in the case of the pitch obtained via EBI treatment, we found that the amount of components with higher molecular weight over 1000 (m/v) similarly increased. Further, the thermal stability and carbon yield at 850 °C of the pitch obtained by EBI were greater than those of samples subjected to thermal treatment at 250 and 300 °C. Highlights: Comparison of the pitches obtained via EBI or non-EBI. The increase of aromaticity in the pitches obtained via EBI. Proof of conversion of aromatic compounds using EBI without catalyst.